AI tool for automatic synthesis of CHP systems - Ostrowski, Ziemowit; Liszka, Marcin; Smołka, Jacek; Ziębik, Andrzej; Nowak, Andrzej J. (Computer Assisted Methods in Engineering and Science, 2007)
Inside the EU countries significant investments are expected in both the electricity production and energy transfers within the next 15 years. Such investments will need the precise decision-making processes, supported with very versatile engineering tools. The major objective of this paper is to propose an application of a new methodology to design power systems in a fully automatic way. The proposed methodology utilizes such artificial intelligence tools like genetic algorithms and expert systems.